SOSIALISASI TERAPI KOMPLEMENTER BUAH NAGA MERAH DALAM MENURUNKAN KADAR KOLESTEROL PADA ANGGOTA KELUARGA DENGAN RIWAYAT HIPERKOLESTEROL DIWILAYAH KERJA UPTD PUSKESMAS MUNJULJAYA KABUPATEN PURWAKARTA - H. Nelson Doloksaribu; Teten Sutendi; Rachma L Varhianti (Bajang Institute, 2021)
Cholesterol is a fatty substance circulating in the body that is produced by the liver and is very important for the body. Excessive cholesterol in the blood will result in the first problems in the blood vessels and brain. Hypercholesterolemia is recorded in more than 160 million people in the world. This study used a descriptive method of research subjects with 1 family patient who had hypercholesterolemia due to blood cholesterol levels in the work area of UPTD Puskesmas Munjuljaya, how to collect data starting from interviews, observations and documentation. The theory taken about the effect of red dragon fruit on hypercholesterolemia according to the journal Maulidiyah, et al 2021. That eating red dragon fruit directly can lower total cholesterol levels. Research conducted by researchers with the application of red dragon fruit therapy for 21 days and consumed 1 time a day conducted on 1 respondent decreased with the results of cholesterol levels from 260 mg / dL to 174 mg / dL. From the results of the research conducted by researchers in line with the journal taken and there was a decrease by doing red dragon fruit therapy